Employees as Individually and Collectively Acting Subjects—Key Contributions from Nordic Working Life Research - Hasle, Peter; Sørensen, Ole Henning (Nordic Journal of Working Life Studies, 2013)
The Nordic countries—Denmark, Finland, Iceland, Norway, and Sweden—are societies that share many features among themselves that also distinguish them from other industrialized countries. The paper poses the question whether the distinct character of the Nordic societies has generated working life research that is clearly distinguishable from similar research in other countries in terms of distinctness in topics, methods, empirical findings, or theoretical concepts. The aim of this paper is to answer this question by identifying, analyzing, and discussing selected key contributions from Nordic working life research to understand how they research and construe the conditions of humans at work with a special focus on the psychosocial well-being of industrial workers. The paper concludes that the key contributions to Nordic working life research have a distinctive emphasis on collective employee voice and autonomy and an extensive use of empirical and actionoriented research methods. Employees are construed not only as workers resisting exploitations from management or as workers pursuing individual careers, but also as members of collectives who share ideas and aspirations and who legitimately influence the management (and research) using cooperation and pressure.